Laser applications in nanotechnology: nanofabrication using laser ablation and laser nanolithography - Makarov, G N (Physics Uspekhi, 2013)
The fact that nanoparticles and nanomaterials have fundamental properties different both from their constituent atoms or molecules and from their bulk counterparts has stimulated great interest, both theoretical and practical, in nanoparticles and nanoparticle-based assemblies (functional materials), with the result that these structures have become the subject of explosive research over the last twenty years or so. A great deal of progress in this field has relied on the use of lasers. In this paper, the directions followed and results obtained in laser nanotechnology research are reviewed. The parameters, properties, and applications of nanoparticles are discussed, along with the physical and chemical methods for their fabrication and investigation. Nanofabrication applications of and fundamental physical principles behind laser ablation and laser nanolithography are discussed in detail. The applications of laser radiation are shown to range from fabricating, melting, and evaporating nanoparticles to changing their shape, structure, size, and size distribution, through studying their dynamics and forming them into periodic arrays and various structures and assemblies. The historical development of research on nanoparticles and nanomaterials and the application of laser nanotechnology in various fields are briefly reviewed.